220k views
4 votes
Can someone help me with this also.

Can someone help me with this also.-example-1
User Beastieboy
by
5.9k points

2 Answers

6 votes

Answer:

(- 9, 6 )

Explanation:

Given the 2 equations

3x - 2y = - 39 → (1)

5x + 2y = - 33 → (2)

Adding the 2 equations, term by term, will eliminate the y- term, that is

8x = - 72 ( divide both sides by 8 )

x = - 9

Substitute x = - 9 in either of the 2 equations and solve for y

Substituting into (2)

5(- 9) + 2y = - 33

- 45 + 2y = - 33 ( add 45 to both sides )

2y = 12 ( divide both sides by 2 )

y = 6

Solution is (- 9, 6 )

User Darren Zou
by
6.5k points
4 votes

Answer:

(-9,6)

Explanation:

User Woong
by
4.6k points